THE LINKAGE BETWEEN FINANCIAL LITERACY AND FINANCIAL DECISION-MAKING WITH THE MEDIATING EFFECT OF INVESTMENT BEHAVIOR - Kashif Bilal Majeed; Asif Khan; Imran Ghaffar; Habib Asghar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This research investigates the linkage between financial literacy and financial decision-making, with the mediating effect of investing behavior in Pakistan’s stock exchange. To achieve this very objectives, PLS-SEM was used to justify relationships on an individual-level survey. As the thumb rule, financial decision-making competence may be enhanced by improving financial knowledge, financial skills, and investing behaviour, thereby encouraging their participation in financial services. Above all else, the indirect influence of financial knowledge and financial attitude on investment decision-making competence is reflected as a most relevant significant tool of financial behaviour. The findings support policy-makers and business experts in identifying the most crucial determinants on financial capability in the context of emerging countries, enabling them to propose policies and refurbished programmes to the good mix potential learners with the package of sound information and required skilled-propelled knowledge studded with the legitimate use of the available financial resources.